Education for reconstruction: A post-apartheid response to the education crisis in South Africa - Manala, Matsobane J. (HTS teologiese studies, 2002)
In this article education is presented as one of the important tools for the reconstruction of the South African society after the demise of apartheid. The kind of education that, in my opinion, will effectively achieve the reconstruction objective, is what I prefer to term “education for reconstruction”. The construct: Education for reconstruction is further developed. It is postulated that Ubuntu Education is the kind of education that will make the grade in the drive to achieve the goal of reconstruction. I focus on the best I believe the envisaged Ubuntu education can bring about. I recommend Ubuntu education which is presented as the promoter of interdependence, loving relationships, caring, mutual respect and commitment. The relation between Ubuntu and the Biblical social values is highligted and the importance thereof for education, indicated. I conclude by urging those who are responsible for the education of the country’s youth not to divorce education from responsibility. I subsequently express the conviction that, if used correctly, Ubuntu education will facilitate the smooth integration of young people into the community, church, industry and the global community.